1975
DOI: 10.2320/matertrans1960.16.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition on Stress Corrosion Cracking of Austenitic Stainless Steels in Boiling MgCl<SUB>2</SUB> Solutions of Various Concentrations

Abstract: The effect of composition on SCC of austenitic stainless steel has been investigated in various boiling MgCl2 solutions. The stress applied was a constant load of 25kg/mm2. The relation between the boiling point of MgCl2 solution (concentration of MgCl2) and the time to fracture was determined. The results obtained are as follows:(1) Commercial stainless steels show the maximum susceptibility to SCC over a certain concentration range of boiling MgCl2 solutions.(2) The sensitized stainless steel suffers intergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The transgranular stress corrosion cracking (TGSCC) of austenitic stainless steels can be explained by the film-induced cleavage, [36][37] or HE mechanism. 17,38 In this test, the sample was immersed in a saturated MgCl 2 solution at 143°C, which provides a slightly acidic environment by the hydrolysis of MgCl 2 following the electrochemical reaction:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transgranular stress corrosion cracking (TGSCC) of austenitic stainless steels can be explained by the film-induced cleavage, [36][37] or HE mechanism. 17,38 In this test, the sample was immersed in a saturated MgCl 2 solution at 143°C, which provides a slightly acidic environment by the hydrolysis of MgCl 2 following the electrochemical reaction:…”
Section: Resultsmentioning
confidence: 99%
“…The cathodic reduction of protons to hydrogen ions on the metal surface will then promote the uptake of hydrogen atoms into the crack tip. 17 It has been found that hydrogen could diffuse and enrich in the crack tips during the rupture of the surface film. 33,37,[39][40] It is suggested that hydrogen can assist the crack propagation during SCC by either the anodic dissolution at the crack tip sustained by the cathodic reduction of hydrogen ions, [41][42] or the martensite phase transformation in unstable austenitic steels resulting from hydrogen absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various alloys display various modes of crack growth and examples have been compiled by Scully [11]. Figure 11.9 shows an example of intergranular and transgranular crack growth on the same alloy but in different concentrations of the same electrolyte [12]. …”
Section: Propagation Of Sccmentioning
confidence: 99%